Platform Design and Electronic Word-of-Mouth Adaptability: A Construal Level Perspective - Chan, Hung-Fai (Sunny) (Curtin University, 2024)
Drawing on the construal level theory, this thesis examines how two platform design features (structural complexity and length requirement) may impact eWOM favourability. Converging evidence from five lab studies and a field study indicates that a structurally complex (vs. structurally simple) design and a high-word-count (vs. low-word-count) design each induce review content lower in eWOM favourability. This research contributes to the bourgeoning eWOM literature by highlighting the significance of review platform design.